Partisipasi Masyarakat dalam Pengembangan Ekowisata Air Terjun Coban Glotak Desa Dalisodo Berdasarkan Perspektif Cohen dan Uphoff - Rice Kurnia Daima; Rohman, Abd.; Dewi Citra Larasati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2026)
Tourism management and development have not been carried out optimally; the community is still positioned as an object, tends to be passive, and lacks a sufficient level of awareness. This study aims to examine and analyze community participation in the development of Coban Glotak ecotourism in Dalisodo Village, Malang Regency. This research was conducted from May to June 2023 using a descriptive qualitative method. The study involved five informants selected purposively, namely the Village Head, Village Secretary, Head of Development Affairs, a community member, and a tourism caretaker. Data were collected through interviews, observation, and documentation, and analyzed using an interactive model consisting of data collection, condensation, data display, and conclusion drawing. The analysis refers to the participation theory of Cohen and Uphoff, which includes participation in decision making, implementation, benefit utilization, and evaluation. Data validity was ensured through technical triangulation. The results indicate that community participation remains partial, limited to consultation in decision making and labor contribution in implementation. The community has not gained significant economic benefits, and participation in evaluation remains low. This study is limited to a single location and a qualitative approach; therefore, the findings cannot be widely generalized.